Social and institutional supports influence on stress management among academic staff in federal universities in South-West Nigeria (2016)
This study examined the combined influence of social (career advice. connectedness and feedbacks appraisals) and institutional (research assistance, promotion, collegiality) protection, friendship and opportunity) supports on the management of stress among academic staff in four selected federal universities in South-West, Nigeria. This study adopted the descriptive survey design. The universities were stratified into existing faculties. The proportional sampling technique was used to select 1000 academic staff Two hypotheses were tested at 0.05 level! of significance. Data were analysed using Pearson product moment correlation and content analysis. Effective social support system coupled with opportunities for promotion and research assistance as well as promotion positively determined the management of stress among academic staff in four(4) federal universities in the South-west Nigeria There is the need to improve upon the social supports while effective institutional supports should he provided to enhance the stress management system among the academic staff In addition conducive and flexible work environment should be ensured.